1998
DOI: 10.1002/mrm.1910390608
|View full text |Cite
|
Sign up to set email alerts
|

Temporal characteristics of oxygenation‐sensitive MRI responses to visual activation in humans

Abstract: Series of single-shot blipped echo-planar images with spin-density weighting and T2* sensitivity (2.0 T, TR = 400 ms, TE = 54 ms, flip angle = 30 degrees) were used to study the temporal response profiles to repetitive visual activation (5 Hz, reversing black and white checkerboard versus darkness) for protocols comprising multiple cycles of a 1.6-s stimulus in conjunction with a 8.4-s or 90-s recovery phase and a 10-s stimulus with a 20-s or 90-s recovery phase. Analysis of the real-time data from all activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 17 publications
3
41
0
1
Order By: Relevance
“…Some reports, mainly from studies performed at high magnetic fields, confirmed the initial dip (Ernst and Hennig, 1994;Menon et al, 1995;Logothetis et al, 1999;Yacoub and Hu, 1999;. Those confirmations, however, remained somewhat isolated because the initial dip, whose amplitude grows more rapidly with the field strength than the positive BOLD response (Yacoub and Hu, 1999), was missed in most of the low-field studies (Fransson et al, 1998;Mandeville et al, 1999a;Marota 1999, but see Yacoub and Hu, 1999) and even in some high-field experiments (Silva et al, 2000); in any case, when investigated with BOLD fMRI, the initial dip appeared to be somewhat elusive (Logothetis, 2000versus Kim, 2000. In addition, doubts were raised with respect to the accuracy of the [Hbr] and the oxyhaemoglobin concentration ͓͑HbO 2 ͔͒ time courses calculated by Malonek and Grinvald in their 1996 paper, since those had been obtained with a classical Beer-Lambert spectroscopic model, which approximates the optical path as constant rather than taking its wavelength dependency into account (Cope et al, 1991;Arridge et al, 1992).…”
Section: The "Initial Dip"; Oxidative Metabolism Debatementioning
confidence: 99%
“…Some reports, mainly from studies performed at high magnetic fields, confirmed the initial dip (Ernst and Hennig, 1994;Menon et al, 1995;Logothetis et al, 1999;Yacoub and Hu, 1999;. Those confirmations, however, remained somewhat isolated because the initial dip, whose amplitude grows more rapidly with the field strength than the positive BOLD response (Yacoub and Hu, 1999), was missed in most of the low-field studies (Fransson et al, 1998;Mandeville et al, 1999a;Marota 1999, but see Yacoub and Hu, 1999) and even in some high-field experiments (Silva et al, 2000); in any case, when investigated with BOLD fMRI, the initial dip appeared to be somewhat elusive (Logothetis, 2000versus Kim, 2000. In addition, doubts were raised with respect to the accuracy of the [Hbr] and the oxyhaemoglobin concentration ͓͑HbO 2 ͔͒ time courses calculated by Malonek and Grinvald in their 1996 paper, since those had been obtained with a classical Beer-Lambert spectroscopic model, which approximates the optical path as constant rather than taking its wavelength dependency into account (Cope et al, 1991;Arridge et al, 1992).…”
Section: The "Initial Dip"; Oxidative Metabolism Debatementioning
confidence: 99%
“…In this transient effect, after the end of stimulation, the BOLD signal drops from the activated state to below the steadystate resting baseline, and then slowly rises back to baseline. If sufficiently long rest periods are not allowed for the response to return to baseline before subsequent stimulation, the poststimulus undershoot is known to cause an apparent shift in baseline [Fransson et al, 1998]. Because the primary focus of this Figure 10.…”
Section: The Bold Responsementioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) is widely used to investigate brain function during different motor tasks and various sensory stimulations in humans (Fransson et al, 1998(Fransson et al, , 1999Hofbauer et al, 2004Hofbauer et al, , 2006Hwang et al, 2005;Olausson et al, 2005;Seung et al, 2005;Elfgren et al, 2006;Pastor et al, 2006). The most commonly used technique relies on blood oxygenation level-dependent (BOLD) contrast, which is indirectly related to neuronal activity (Ogawa et al, 1993;Heeger and Ress, 2002;Thompson et al, 2003;Mukamel et al, 2005;Niessing et al, 2005).…”
Section: Introductionmentioning
confidence: 99%